PENGARUH RASIO LIKUIDITAS, LEVERAGE KEUANGAN, OPERATING INCOME, DAN EFEKTIVITAS KOMITE AUDIT TERHADAP FINANCIAL DISTRESS - Yanuar, Yayan (Sekolah Menengah Kejuruan (SMK) Pustek, 2018)
This study aims to determine the effect of liquidity ratios, financial leverage, Operating income, and audit committee effectiveness on  financial distress. Liquidity ratio, financial leverage, Operating income and audit committee effectiveness as independent variable and financial distress as dependent variable. This study uses the basic theory of agency theory (agency theory). This research is a quantitative research using secondary data obtained from Indonesia Stock Exchange (IDX) during period 2014-2016. The population in this study is a manufacturing company listed on the Indonesia Stock Exchange. The sample of this study consists of 37 manufacturing companies listed on the Indonesia Stock Exchange 2014-2016 which is determined through purposive sampling. Data analysis technique used is logistic regression test by using SPSS version 22. The results of this research are (1) liquidity ratio has no significant effect on financial distress, (2) financial  leverage has no significant effect on  financial distress, (3) Operating income has significant effect on financial distress, (4) the size of the audit committee has a significant effect on  financial distress, (5) audit committee meetings has nosignificant  effect on financial distress, and (6) liquidity ratio, financial leverage, Operating income, audit committee size, and audit committee meeting simultaneously have significant effect on financial distress